Technological Innovations in Vector-Borne Disease Control and Their Relationship with Public Health - Fairul Kader; Astri Ivo; Manli Desri Helden; Ainun Muthmainnah (Journal of Epidemiology and Health Science, 2026)
Background: Diseases transmitted by vectors remain a major challenge to public health in Indonesia. Continuous use of chemical insecticides has led to resistance, while climate change and vector behavior further exacerbate disease transmission. Therefore, innovative, effective, and sustainable technologies are needed to support community-based vector control efforts. Objective: To review various technological innovations in vector-borne disease control and their relationship with improving public health based on literature from the past five years. Methods: This study is a literature review employing a systematic and narrative approach. The search was conducted through the PubMed, Scopus, Google Scholar, Garuda, and Indonesia OneSearch databases using the keywords “vector control technology innovation” and “public health.” Articles included were publications from 2020–2025 that were relevant to the topic. Results: From the 20 selected articles, five major innovations were identified: the Wolbachia technique, Sterile Insect Technique (SIT) and gene drive, autodissemination using pyriproxyfen, plant-based biolarvicides utilizing local resources, and digital systems based on IoT and GIS. These innovations have been shown to reduce vector density and the incidence of diseases such as dengue and malaria, as well as enhance community participation. Conclusion: Innovative technologies have proven to be more environmentally friendly and efficient compared to conventional methods. Their successful implementation requires policy support, infrastructure readiness, and cross-sector collaboration within the framework of Integrated Vector Management (IVM). Keywords: Technological innovation, vector control, public health, Wolbachia, autodissemination.